David Michael Smith. Pocket Museum: Ancient Greece. - Meens, Anna (Journal of Greek Archaeology, 2018)
The new ‘Pocket Museum’ series by Thames & Hudson was launched in the summer of 2017 with the appearance of two volumes, Ancient Greece and Ancient Rome. In the meantime, a third addition to the series has appeared in March 2018, Ancient Egypt. The books in this series are aimed at presenting artefacts housed in museums all over the world side by side in an illustrated history.